Rationalitetens indfoldning. Rumopfattelsen i Peter Eisenmans arkitektur - Pedersen, Claus Peder (Tidsskriftet Antropologi, 2019)
The article considers a contemporary approach to architecture in a pluralistic world. This is done through a discussion of the work of the American architect Peter Eisenman. In his critique of objectivist spatial categories, Eisenman articulates an architecture based on a folded space. Parallels are drawn to the French philosopher Gilles Deleuze and his considerations of Leibniz’s philosophy of folds. The article relates Peter Eisenman’s highly individual architectural method to the common cultural space of architecture. It concludes that Eisenman’s attempt to form non-rationalistic spatial and architectural categories functions only on a metaphorical level. Finally the article describes other approaches to folded and non-linear space, including theories developed by the architect Greg Lynn.